2020
DOI: 10.1007/s00420-020-01591-w
|View full text |Cite
|
Sign up to set email alerts
|

Health and motivation as mediators of the effects of job demands, job control, job support, and role conflicts at work and home on sickness presenteeism and absenteeism

Abstract: Purpose The first objective was to contribute to a better understanding of the contrasting and paradoxical results in studies of work environment factors and sickness presence and sickness absence. A second objective was to examine if, and under what conditions, employees choose to replace sickness absence with sickness presence, i.e., so-called substitution. Methods The study utilizes a large body of cross-sectional questionnaire data (n = 130,161) gathered in Sweden from 2002 to 2007 in connection with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…The measure used, a validated and reliable (α.70) [ 16 ] work motivation scale, was first introduced by Sjöberg and Lind [ 15 ], and has been used in other studies [ 41 , 42 , 43 , 44 , 45 ]. A short, validated and reliable version of the scale was developed [ 16 ] and has been used in several studies [ 44 , 45 , 46 , 47 ]. In this study, a similar short version of the work motivation scale was used.…”
Section: Methodsmentioning
confidence: 99%
“…The measure used, a validated and reliable (α.70) [ 16 ] work motivation scale, was first introduced by Sjöberg and Lind [ 15 ], and has been used in other studies [ 41 , 42 , 43 , 44 , 45 ]. A short, validated and reliable version of the scale was developed [ 16 ] and has been used in several studies [ 44 , 45 , 46 , 47 ]. In this study, a similar short version of the work motivation scale was used.…”
Section: Methodsmentioning
confidence: 99%
“…Research has identified a variety of factors related to attendance behaviors that are under the control of employers. To name just a few, the importance of social support ( Saijo et al, 2017 ; Nielsen et al, 2019 ; Yang et al, 2019 ; Aronsson et al, 2020 ), attendance cultures or climate ( Thun et al, 2013 ; Løset et al, 2018 ; Mach et al, 2018 ; Martinez et al, 2018 ; Ferreira et al, 2019 ; Ruhle and Süß, 2019 ), reward systems ( Della Torre et al, 2015 ; Rostad et al, 2017 ), and working conditions ( Gerich, 2014 ; Jourdain and Vézina, 2014 ; Yang et al, 2016 ; Ferreira, 2018 ) should be noted here. For example, it is reasonable to assume that employees will stay home in the event of illness if they know that their replacement is well arranged ( Miraglia and Johns, 2016 ) and they do not have to fear that their absence will incur the anger of their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…In general, other aspects being equal, the sickness absence pattern over the years shows that high social support was related to somewhat lower sickness absence. Recent research has shown that high social support may have a paradoxical effect on health and sickness absence ( Aronsson et al, 2021 ). Social support is supposed to lower sickness absence through its health effects but may also raise the motivation to go to work when ill, which in the long run may harm the health and raise sickness absence.…”
Section: Summary and Commentsmentioning
confidence: 99%
“…Sickness absence reflects the health of the working population but the relationship between illness and sickness absence is variable. Research has identified several factors that influence the association such as sickness presenteeism ( Aronsson et al 2000 , 2021 ), use of sickness absence as an illness prevention strategy ( Kristensen, 1991 ), job insecurity ( Ferrie et al, 2001 ; Virtanen et al, 2003 ) and different thresholds for sickness absence between occupations ( Andersen et al, 2012 ). The role of sickness absence compensation levels may also depend on which time perspective is chosen ( Sjöberg, 2017 ).…”
Section: Introductionmentioning
confidence: 99%